Voodoo versus Fishing Committees: The Role of Traditional and Contemporary Institutions in Fischeries Management - Elena Briones Alonso; Romain Houssa; Marijke Verpoorten (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the co-existence of two community-based institutions for fisheries management in Benin: a traditional institution embedded in the Voodoo religion and a recent secular institution in the form of fishing committees. Using household survey data on fishing activities, we find that rules of both institutions have a statistically significant but small impact on the use of unsustainable fishing gear. We further find that Voodoo fishers who break the traditional Voodoo-based rule follow the fishing committee rule to the same extent as other fishers. This finding is consistent with a possible transition from the traditional Voodoo-based institution to the secular fishing committee institution. More research is needed to fully assess the effectiveness of, and interactions between, the two institutions.
Keywords: 330; community-based natural resource management; institutions; religion; Voodoo; fisheries; Benin